Organizational commitment and feeling of permanence of professionals in public and private organizations in Lima - Loli P, Alejandro (2015)
The study aims to meet organizational commitment and feelings of permanence of professionals in public and private organizations in Lima. The sample consisted of 221 employees, most of them many professionals who are enrolled on graduate studies in higher education centers. A questionnaire was applied to them, the results indicate that there is a favorable trend of organizational commitment as feelings of stay in institutions where they work. On the other hand, we find that there is significant and positive association of affective commitment to the feeling of permanence, while the latter is not associated with the commitment of convenience. Meanwhile, the relationship with socio demographic variables explored is varied, affective commitment is related to age, marital status, seniority and length of service in current position; the commitment of convenience to age and marital status and the feeling of permanence only to the origin of the participants; in other words, they are differentiating variables.